The association between the percentage of female law enforcement officers and rape report, clearance, and arrest rates: a spatiotemporal analysis of California - Kaplan, Zoe (Journal of interpersonal violence, 2024)
Rape is an underreported violent crime that frequently remains uncleared (open) in the legal system. Rape disproportionately affects women, with 91% of rape victim-survivors estimated to be female. However, law enforcement agencies, the entry point into the criminal justice system, are predominantly comprised of male officers. According to the theory of representative bureaucracy, groups with greater representation in a bureaucratic system are more likely to have their interests protected. This study aims to determine if California law enforcement agencies with a higher percentage of female officers are more likely to have higher rates of rape reporting, clearances, and arrests. No previous study has examined this relationship using statewide data. Crimes and Clearances, Monthly Arrest and Citation Register, and Uniform Crime Reporting data for California (2013–2016) were aggregated into 499 Law Enforcement Reporting Areas (LERA). Bayesian space-time Poisson regressions controlling for LERA demographics and crime produced scaled relative rates for three outcomes: (a) rape report rate: number of reports relative to population ages 18+; (b) rape clearance rate: number of clearances relative to reports; and (c) rape arrest rate: number of arrests for rape relative to reports. A 5% increase in the percentage of female officers within an agency was associated with a 6.2% increase in the rape report rate (ARR: 1.062, 95% credible interval (CI) [1.048, 1.077]), a 2.9% decrease in the clearance rate (ARR: 0.971 95% CI [0.950, 0.993]), and no change in the rape arrest rates (ARR: 1.010; 95% CI [0.981, 1.039]) across all LERA. Thus, increased female officer representation was associated with an increase in rape reporting rates but associated with a decrease in rape clearance rates. The theory of representative bureaucracy was only partially supported, and these relationships may not be causal. The quantity of rape reports received by an agency, employment and promotion practices of agencies, and victim-survivor’s attitudes toward officer’s gender should also be considered.